2016
DOI: 10.1111/jvim.14592
|View full text |Cite
|
Sign up to set email alerts
|

Explanation and Elaboration Document for the STROBE‐Vet Statement: Strengthening the Reporting of Observational Studies in Epidemiology—Veterinary Extension

Abstract: The STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement was first published in 2007 and again in 2014. The purpose of the original STROBE was to provide guidance for authors, reviewers, and editors to improve the comprehensiveness of reporting; however, STROBE has a unique focus on observational studies. Although much of the guidance provided by the original STROBE document is directly applicable, it was deemed useful to map those statements to veterinary concepts, provide v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 162 publications
0
44
0
Order By: Relevance
“…Our study was an observational retrospective cohort study . The Strengthening the Reporting of Observational Studies in Epidemiology Vet Statement (Veterinary Extension) was used to report this study (Data S1).…”
Section: Methodsmentioning
confidence: 99%
“…Our study was an observational retrospective cohort study . The Strengthening the Reporting of Observational Studies in Epidemiology Vet Statement (Veterinary Extension) was used to report this study (Data S1).…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of 100 observational studies in preharvest food safety found that only 38% used one of the “big three” labels (case‐control, cohort, and cross‐sectional studies) to describe the study design used . The recent publication of STROBE‐Vet, a reporting standard for observational studies in animals, may improve the consistency of methodological reporting going forward and make it more feasible to identify such study designs consistently with a search strategy …”
Section: Discussionmentioning
confidence: 99%
“…Our finding that information on the selection methods for study subjects was not reported in all studies is of concern. Although not specific to descriptive cohort designs, the STROBE‐Vet guidelines recommend that information on the target, source, and study populations be reported; these guidelines also provide information on the level of detail that should be included …”
Section: Discussionmentioning
confidence: 99%